Dual ACL Ganglion Cysts: Significance of Detailed Arthroscopy. (7th October 2014) - Mittal, Samarth; Singla, Amit; Nag, H. L.; Meena, Sanjay; Lohiya, Ramprakash; Agarwal, Abhinav
Abstract : Intra-articular ganglion cysts of the knee joint are rare and most frequently are an incidental finding on MRI and arthroscopy. Most of the previous studies have reported a single ganglion cyst in the knee. There have been previous reports of more than one cyst in the same knee but not in the same structure within the knee. We are reporting a case of dual ACL (anterior cruciate ligament) ganglion cysts one of which was missed on radiological examination but later detected during arthroscopy. To the best of our knowledge, no such case has been reported in the indexed English literature till date.